1989
DOI: 10.1128/jb.171.5.2889-2893.1989
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of arcA, arcB, and cpxA mutant phenotypes of Escherichia coli by sex pilus formation and enzyme regulation

Abstract: In Escherichia coli, mutations in arcA (dye) or arcB anaerobically derepress the synthesis of a multitude of enzymes of aerobic function, and mutations in arcA or cpxA impair F-pilus formation. It is thought that arcA encodes a promoter-recognizing protein, whereas arcB and cpxA encode sensor proteins which interact with the arcA product. In this study we found that anaerobic growth of a wild-type F' strain decreased the synthesis of both the enzymes and the pilus. Although the two arcA mutants examined were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…In the current model, the signal is acquired by the integral membrane protein ArcB, which then transduces the information to a form that can be read by the ArcA protein, which is the actual genetic regulator (15,16,19). We show here that tra gene expression is only slightly dependent on ArcB function(s), in agreement with earlier, qualitative observations by luchi et al (17). If ArcB is required to elicit ArcA activity, this result implies that the Arc and Sfr functions of the arcA gene product are separately regulated.…”
Section: Resultssupporting
confidence: 80%
“…In the current model, the signal is acquired by the integral membrane protein ArcB, which then transduces the information to a form that can be read by the ArcA protein, which is the actual genetic regulator (15,16,19). We show here that tra gene expression is only slightly dependent on ArcB function(s), in agreement with earlier, qualitative observations by luchi et al (17). If ArcB is required to elicit ArcA activity, this result implies that the Arc and Sfr functions of the arcA gene product are separately regulated.…”
Section: Resultssupporting
confidence: 80%
“…Aerobic and anaerobic regulation in E. coli is mediated in part by the ArcA/ArcB two-component system (13). A second sensor protein, CpxA, can also interact with ArcA (13,14) but in response to some signal other than that detected by ArcB. In a third example, the gene encoding a novel sensor protein, barA, was identified that shares a high degree of homology to both EnvZ and OmpR (25).…”
Section: Discussionmentioning
confidence: 99%
“…The arcA2 and arcB1 null alleles linked to Tn10 insertions (Iuchi et al, 1989b) were introduced into DS941 by P1 transduction. DS941 arcA2 was found to be almost completely defective in recombination at psi, whereas DS941 arcB1 was found 1 2 3 4 5 6 7 8 9 10 1 2 3 4 5 6 7 8 9 10 S P S P Fig.…”
Section: Identification and Genetic Characterization Of Mutants Defecmentioning
confidence: 99%